The Application of Factor Analysis to Determine the Parameters of Planning Work-Zone in the Road Repair and Maintenance - Khabiri, Mohammad Mehdi (International Journal of Sustainable Construction Engineering and Technology, 2016)
Building and maintaining transport infrastructure is essential for economic and social development of each country. The high costs of repair and maintenance of the existing road networks required to manage the road repair and maintenance and systematic planning for this process. The scope of where the operational performance of road repair and maintenance are carried is called work zone. The measures are carried in the work zone caused traffic and increased the likelihood of traffic accidents. For this reason, in addition to repair and management operations, the traffic guidance and control with the aim of accelerating projects implementation, safety of personnel as well as users is important.  In this regard, a number of related staff were selected by the simple random sampling method and Kukran formula and were asked them to respond to a questionnaire with approved reliability and validity. The results of questionnaires were used in factor analysis method in three dimensions form include personal safety, environmental protection and cost reduction as the main factors. In this study, in the first step by a questionnaire  tried  to identify and summarize the key factors among the effective factors on the successfulness of pavement maintenance and road infrastructure projects  and then in the second  step, by factor analysis  tried to  form a matrix to evaluate these factors. According to standard of factor analysis method the factor 1 to factor 3 with 85% had the greatest impact on the performance of pavement maintenance and repair activities. These factors can be summarized in a set of measures such as restrictions on the movement of heavy vehicles in the scope of work zone, work in an appropriate hour and dividing the high tasks into smaller tasks.